An examination of sport tourists' profiles and motives as for visiting Langkawi - Hamdan, Nurul Shahida; Yusof, Aminuddin (IDOSI Publications, 2014)
Understanding the peoples’ motives is important in promoting tourism, since it provides a better explanation of the motive behind the motive behavior and enable tourism planner and marketer to predict tourists’ actions. The present study aimed to address sport tourists’ profiles in order to determine sport tourists’ motives. Data were collected quantitatively from 248 subjects in Langkawi using the shorten version of Leisure Motivation Scale develop by Beard and Ragheb (1983). Data were analyzed using descriptive statistic and t-test. Majority of the respondents (74.6%) were domestic sport tourists. Both domestic sport tourists and foreign sport tourists found a significant difference towards their motives while visiting Langkawi. Domestic sport tourists are more motivated to have social (M = 3.949, SP =.805; t (246) = 3.942, p =.000) and competence mastery (M = 3.942, SP =.799; t (246) = 2.575, p =.011) compared to foreign sport tourists. The results indicate that domestic sport tourists and foreign sport tourists travelled to Langkawi as they want to social with their family and friends. Based on the findings of the study, it can be used by sport tourism industry to implement effective market segmentation in Langkawi.